Digital communication in health promotion in handling tuberculosis sputum - Makalew, Linda Augustien; Rambi, Elne Vieke; Makaminan, Muhammad Ali (Jurnal Teknologi Laboratorium, 2021)
The Covid-19 pandemic that has caught the attention of not only Indonesia but the rest of the world. The 3M movement, namely using masks, washing hands and keeping a distance to minimize the transmission of tuberculosis, is very useful for the eradication of TB tuberculosis. However, this is a challenge in itself for microscopic officers at the Microscopic Reference Center (MRC) in education and handling of sputum for tuberculosis patients who are currently being treated. The purpose of this study was to test VisKomLAM 1, 2, 3 and 4 in bridging communication between officers in sputum management education for tuberculosis sufferers at each examination during the Covid-19 pandemic. The research locations took MRC Tuminting, Wawonasa and Tikala Baru in Manado City and MRC Telaga in Gorontalo District. Analysis with paired t test showed a significance below 5%, which means that VisKomLAM 1, 2, 3 and 4 can bridge education from officers to tuberculosis sufferers in the Covid-19 pandemic era. It is recommended that health workers always strive to promote tuberculosis health in achieving tuberculosis elimination by 2050